Cycloalkyl Fused Dibenzofuran Derived Green Ir(III) Complexes Possessing High Horizontal Emitting Dipole Orientation Ratios and Color Stability at High Doping Concentrations. Issue 23 (3rd October 2022) - Kim, Seung Chan; Hong, Wan Pyo; Lee, Jun Yeob
Abstract: In this study, the photophysical characteristics and electroluminescence of three green Ir(III) complexes with newly created cycloalkyl fused dibenzofuran ligands are examined. The results demonstrate that the cycloalkyl fused dibenzofuran ligand can modify the intermolecular interactions and alter the horizontal emitting dipole orientation ratios of dopants in phosphorescent organic light‐emitting diodes (PhOLEDs). One of the three phosphors, Ir(TBF)2 (mppy), shows high photoluminescence quantum yield of 0.96 and a high horizontal emitting dipole orientation ratio of 0.80. Therefore, an optimized PhOLED using Ir(TBF)2 (mppy) exhibits a peak external quantum efficiency (EQE) of 27.1% and a very small efficiency roll‐off with a high EQE of 25.1% at 10 000 cd m −2 . It is significant that the high EQE device maintains the CIE chromaticity coordinates over a wide doping concentration range (3–10 wt%), thus creating new possibilities for the dopant design strategy for the practical use of PhOLEDs. Abstract : Three green Ir(III) complexes with newly created cycloalkyl fused dibenzofuran ligands demonstrate that the cycloalkyl fused dibenzofuran ligand can modify the intermolecular interactions and alter the horizontal emitting dipole orientation ratios of dopants.